4CPS-103 Evaluation of health outcomes of daratumumab in monotherapy in adult patients with relapsed refractory multiple myeloma. (March 2019) - Alarcon-Payer, C; Martínez-de la Plata, JE; Cano Domínguez, S; Clavero Sánchez, ME; Ríos Tamayo, R; Jurado Chacón, M; Jiménez Morales, A
Abstract : Background: Immunotherapy has broken new ground in the treatment of multiple myeloma, with the introduction of monoclonal antibodies into the therapeutic arsenal, representing a paradigm shift in treatment. Daratumumab is a human monoclonal antibody IgG1κ, which binds to the CD38 protein that is expressed at a high level on the surface of multiple myeloma tumour cells. Purpose: To evaluate the health outcomes of daratumumab in monotherapy in the treatment of adult patients with relapsed refractory multiple myeloma (RRMM), who have previously received a proteasome inhibitor and an immunomodulatory agent, and who have experienced disease progression in the last treatment. Material and methods: Prospective observational study conducted over a period of 2 years in a third-level hospital. Eleven patients diagnosed with RRMM have been analysed. To evaluate the measurement of health outcomes, the following variables were measured: age, sex, number of previous lines, daratumumab cycles received, progression-free survival (PFS) and adverse reactions. Results: Eleven RRMM cases were analysed, (80%: men; 20%: women). The mean age was 63 years. The health outcomes measured in our clinical practice were: 50% of the patients received daratumumab in monotherapy in the third line, 30% in the fourth line and 20% in the sixth and seventh line. The mean number of daratumab cycles was seven, except for one patient who has now completed cycle 20. The median PFS was 4 months. Only mild gastrointestinal adverse reactions (nausea and vomiting) were observed (20% of patients). The correct premedication was performed before and after daratumumab infusion, including 10 mg oral montelukast (first infusion) and respecting the infusion times according to the technical datasheet. Conclusion: Health outcomes of daratumumab in monotherapy for the treatment of patients with RRMM are similar to those published in the combined trial gene 501 and SIRIUS. According to recent publications, daratumumab is likely to be more effective in combination with other drugs. Daratumumab is well tolerated in most patients and is therefore considered a safe treatment. Reference and/or acknowledgements: Usmani S, et al. Clinical efficacy of darzalex monotherapy in patients with heavily pretreated relapsed or refractory multiple myeloma. Blood 2016;128:37–44. No conflict of interest.